Eletromagnetic fields prevision in microwave dryer using computational fluid dynamics (Revista Brasileira de Iniciação Científica, 2021)
The unit operation of microwave drying is one of the most complex existing, having a high degree of complexity in the dimensioning and scale-up of cavities. This work aimed to verify the behavior of electromagnetic and thermal fields in a microwave dryer, checking the influence of the dimensions of the cavity and the waveguide and their positioning. It was observed that the number of hotspots and the intensity of the electromagnetic field vary with the length of the waveguide and the dimensions of the cavity. It is concluded that the simulations had good agreement with experimental, being favorable for an optimization and scale-up of dryers.
Keywords: Simulation. CFD. Maxwell equations. Electromagnetic Fields.